Properties of finger joint by different species and adhesive / Nik Muhammad Ashraf Nik Soh - Nik Soh, Nik Muhammad Ashraf (2014)
The properties of finger joint by different species and adhesive has been conducted. The aims of the study is to find out the strength properties of finger joint using Acacia mangium, Endospermum diadenum, and Neolamarclda cadamba species using PVAc and Epoxy adhesive whether suitable for jointing application or not. The average moisture content of wood materials used for the preparation of test samples was determined as 12%. Then the sample size was cut into 20 x 20 x 160 mm where any natural defects such as knots that occurred were removed according to EN:385:2001 and EN:408:2003. From the bending strength for MOE and MOR, it can be concluded that finger joint from Acacia mangium, Endospermum diadenum, and Neolamarclda cadamba species using by types of adhesive (polyvinyl acetate and Epoxy) can successfully be produced as the main source of raw materials for finger joint.